A clínica fonoaudiológica e a fala holofrásica de uma adolescente com debilidade mental - Pereira, Maria Rosirene Lima (2011)
Introduction: This work focuses on theoretical and clinical issues involving holophrase from the perspective of the subject constituted in and through language, to direct our attention to the mentally handicapped in its alienation to the Other. Aim: To investigate the holophrastic speech of a teenager with mental debility. Method: The speech data of this adolescent were extracted from clinical material of therapy sessions, supplemented by their clinical and symbolic history. The data analysis was supported by the Language Symptoms Organization Model. In particular, there has been the observation of the use, by the speech therapist, of the target procedure of sanction, in its impact on the recognition or denial of the subject and the signifier, coupled with listening to the speech of the teenager. This way, the holophrastic speech had its enigmatic specificity questioned from the uniqueness of the clinical material, whether in the data literalness, in listening to the sound and amorphous mass that constitutes it. Results and Conclusions: The results support the hypothesis that holophrastic speech, to the speech therapy clinical practice, would be the agglutination of unintelligible segments that are presented as an amorphous mass and noise formed by an admixture of signifiers, heard as distorted, welded or without pause between each other. Despite their structural and functional specificity, holophrastic speech has its operation submitted to the order of language itself, in articulation with the individual event of the subject with mental debility talk